2013
DOI: 10.1371/journal.pone.0055646
|View full text |Cite
|
Sign up to set email alerts
|

Volume-Sensitive Anion Channels Mediate Osmosensitive Glutathione Release from Rat Thymocytes

Abstract: Glutathione (GSH) is a negatively charged tripeptide, which is a major determinant of the cellular redox state and defense against oxidative stress. It is assembled inside and degraded outside the cells and is released under various physiological and pathophysiological conditions. The GSH release mechanism is poorly understood at present. In our experiments, freshly isolated rat thymocytes were found to release GSH under normal isotonic conditions at a low rate of 0.82±0.07 attomol/cell/min and that was greatl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 71 publications
3
27
0
Order By: Relevance
“…These results suggest that lower levels of stretch may trigger ROS production in the cytosol, as well to deplete intracellular GSH. It is also possible that stretch might be affecting GSH synthesis and metabolism or that GSH depletion might also be mediated by stretch activated efflux pathways (Franco and Cidlowski, 2012, Sabirov et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that lower levels of stretch may trigger ROS production in the cytosol, as well to deplete intracellular GSH. It is also possible that stretch might be affecting GSH synthesis and metabolism or that GSH depletion might also be mediated by stretch activated efflux pathways (Franco and Cidlowski, 2012, Sabirov et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…For patch-clamping, the cells were cultured in suspension under mild stirring during 3-5 h. All animal experiments were conducted in accordance with the ARRIVE guidelines and approved by the Bioethics Committee of the Institute of Biophysics and Biochemistry. The isolation of thymic lymphocytes (thymocytes) was performed as described previously (Kurbannazarova et al, 2003(Kurbannazarova et al, , 2008(Kurbannazarova et al, , 2011Sabirov et al, 2013). Briefly, the 6-8 weeks old rats, kept in vivarium on an average diet, were anaesthetized with halothane or diethyl ether and painlessly euthanized by cervical dislocation.…”
Section: Cellsmentioning
confidence: 99%
“…In order to test this possibility, we employed the immature thymic lymphocytes which possess fully functional volume regulation machinery (Arrazola et al, 1993;Kurbannazarova et al, 2003;Soler et al, 1993). We have previously shown that thymocytes express the VSOR channels with the same biophysical and pharmacological profile as other cell types, and that VSOR blockers completely abolish RVD in these cells (Kurbannazarova et al, 2011;Sabirov et al, 2013). Therefore, we supposed that tannin preparations might affect the volume regulation in thymocytes.…”
Section: Tannin Preparations Inhibit Thymocyte Volume Regulation Undementioning
confidence: 99%
“…The size of the pore was estimated based on the fit of the relative permeabilities of inorganic anions with known radii, or derived from electrophysiological recordings in the presence of pore permeating or blocking sulfonic-calix arenes and polyethylene glycol molecules with various diameters [51, 52, 200]. The VRAC pore may be suitable for conducting molecules as large as ATP [24, 85] and the tripeptide glutathione [178]. This channel poorly discriminates between various anions and neutral molecules due to the weak charge interactions of transported molecules with the amino acid moieties lining its vestibule.…”
Section: Introduction: General Properties and Physiological Significamentioning
confidence: 99%